PERILAKU PETANI DALAM BERUSAHATANI PADI PANDANWANGI (Kasus di Kabupaten Cianjur Jawa Barat) - Yayat Sukayat; Dika Supyandi; Mahra Arari Haryanto; Rani Andriani Budi Kusumo (Universitas Galuh, 2022)
Cianjur Regency is known as the top ten rice producers in West Java, precisely in the fifth position. Rice from Cianjur is not only known at the local level, but also known at the regional and even national level. One of the well-known rice varieties is the pandanwangi variety, namely the local bulu variety (javanica) Cianjur Agriculture Service, 2011. This rice variety has several advantages, in addition to delicious taste, pandanus fragrance and the price is much more expensive than premium rice. However, recently the pandanwangi rice planting area continues to decrease, even in 2017 the harvest area is only 14 930 hectares. This phenomenon indicates that there is a discrepancy between the behavior of farmers and the support of the government, which makes pandanwangi rice an icon of the city of Cianjur. The question arises how the behavior of farmers in farming pandanwangi rice. The purpose of this study was to determine the perceptions and motivations of farmers to plant pandanwangi rice; and farmers' income from pandanwangi rice farming. Design This study uses a quantitative design with a survey technique on 88 farmers in Warungkondang District, Cianjur. The results of the research on farmers' perceptions of the geographical environment are very supportive; government support is very good, and the motivation of farmers to plant fragrant pandan rice in addition to maintaining the availability of household food, has made pandanwangi an icon of the city of Cianjur.